Ralph Willis address to the National Press Club on 11 May 1994 - Willis, Ralph, 1938-; National Press Club (Australia) (1994)
Following the release of the 1994/95 Budget, Ralph Willis, the Treasurer, re-emphasises his governments' commitment to the unemployed and deficit reduction, pointing to Australia's continued strong economic growth and forecast increased business investment.
Also available online
Transcript unavailable.
Keywords: Willis, Ralph, -- 1938-; Politicians -- Australia; Budget -- Australia; Australia -- Economic conditions -- 1990-2001.; Australia -- Economic policy -- 1990-2001.; Federal politicians